(untitled) (Psychology Travelogs, 2024)
The article discusses the results of an empirical study on the psychological characteristics of the professional development of future marketing managers. The research process involved the use of various methodologies to study the following aspects: the level of student motivation for achievement and the avoidance of failure, attitudes toward the surrounding world, other people, themselves, the basis of their worldview, the core of motivation for life activities, the basis of their life concept, and their "philosophy of life." Hierarchical structures of terminal and instrumental values of future marketing managers were studied with the aim of investigating the orientation of personality and determining their attitudes toward the surrounding world, other people, themselves, perception of the world, key motives for actions, and the basis of their "philosophy of life." Career orientations such as professional competence, management, autonomy, job stability, residential stability, service, challenge, lifestyle integration, and entrepreneurship were investigated. The study also examined important professional qualities of marketing managers, such as communicative and organizational skills, as well as attributes of the emotional and volitional sphere. An interesting and crucial aspect of the research was diagnosing the level of empathy in future marketing managers and the development of scales for reactive and personal anxiety. The culmination of the research was the diagnosis of the "emotional intelligence" of future marketing managers to understand the level of emotional awareness, self-regulation, self-motivation, empathy, recognition of others’ emotions, and overall emotional intelligence development. Respondents’ answers within the survey provided insights into the most significant factors, according to them, that contribute to a favorable socio-psychological climate within the team, as well as the primary conditions influencing the professional development of future marketing managers and the personal characteristics that determine effective advancement in the hierarchical structure.